2022
DOI: 10.1093/humupd/dmac033
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated epigenetic changes in mammalian sperm: implications for offspring health and development

Abstract: BACKGROUND Modern reproductive behavior in most developed countries is characterized by delayed parenthood. Older gametes are generally less fertile, accumulating and compounding the effects of varied environmental exposures that are modified by lifestyle factors. Clinicians are primarily concerned with advanced maternal age, while the influence of paternal age on fertility, early development and offspring health remains underappreciated. There is a growing trend to use assisted reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 174 publications
0
35
0
Order By: Relevance
“…It has also been hypothesized that age-induced changes in the sperm epigenome are profound and probably irreversible. However, to date, there has been little research on the effects of age on H19 gene methylation [ 48 ]. A study of 196 adolescent and 176 middle-aged twins failed to find a correlation between age and methylation changes in the DMR of the H19/IGF2 locus.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been hypothesized that age-induced changes in the sperm epigenome are profound and probably irreversible. However, to date, there has been little research on the effects of age on H19 gene methylation [ 48 ]. A study of 196 adolescent and 176 middle-aged twins failed to find a correlation between age and methylation changes in the DMR of the H19/IGF2 locus.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have signified the role of aging oocytes which present with oocyte cytoplasmic volume decreasing ( 34 ) and mitochondrial dysfunction ( 35 ), as well as epigenetic modifications occurred in genes regulating growth and metabolism, such as histone acetylation and DNA methylation ( 36 ). Similar epigenetic changes with increasing paternal age ( 37 39 ) may also be associated with changes of metabolic phenotype in offspring, but the specific mechanism remained unclear. In addition, the protective effect of older paternal age we found is possibly because that older fathers are more likely to be wealthier and better educated compared with younger fathers, which enable them to provide a better and healthier child-bearing environment for children ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In brief, using random stratified cluster sampling method, 12-16 primary and secondary schools were selected in each province and 44,436 participants with complete information of maternal age and paternal age were included. In present study, we enrolled 39,190…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The accumulated studies on obesity using mouse models reported a diverse set of mature sperm miRNA candidates implicated in inducing metabolic disorder in the offspring. Surprisingly, only a few miRNA candidates overlapped between the studies, and some showed a contradictory expression profile as well, possibly owing to the greater length of time each study employed in establishing the obese models (10 w, 17 w, 20 w, 26 w); the change in the sperm sncRNA profile concomitant with aging [ 105 ] might have shrouded the key players in response to the excessive change in diet. Interestingly, miR-19b alone was found to play a larger role in shaping the offspring’s health, as the microinjection of synthetic miR-19b to zygote could partially recapitulate the western-like diet phenotypes in the offspring [ 99 ].…”
Section: Alteration Of the Sperm Sncrna Transcriptome In Response To ...mentioning
confidence: 99%